“Pink Pattern” Visualized in Magnifying Endoscopy With Narrow-Band Imaging Is a Novel Feature of Early Differentiated Gastric Cancer: A Bridge Between Endoscopic Images and Histopathological Changes - Chen, Shengsen; Yu, Jiangping; Ruan, Rongwei; Li, Yandong; Tao, Yali; Shen, Qiwen; Cui, Zhao; Shen, Cheng; Wang, Huogen; Jin, Jiayan; Chen, Ming; Jin, Chaohui; et al. (Frontiers in Medicine, 2021)
Background: A pink color change found occasionally by us under the magnifying endoscopy with narrow-band imaging (ME-NBI) may be a special feature of early gastric cancer (EGC), and it was named as “pink pattern”. The purposes of this study were to reveal the relationship between the “pink pattern” and the cytopathological changes of gastric cancer cells, and explore whether the pink pattern was useful for the diagnosis of EGC. Methods: The color features of ME-NBI images and pathological images on gastric cancerous mucosal surface were extracted and quantized, and then the cosine similarity was calculated to evaluate the correlation between the pink pattern and the nucleus-to-plasm ratio of cancerous epithelial cells. Two diagnostic tests were performed by 12 endoscopists using stored ME-NBI images of 185 gastric lesions to investigate the diagnostic efficiency of “pink pattern” for EGC. The diagnostic values such as area under curve (AUC), accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) between test 1 and test 2 were compared. Results: The cosine similarity in 20 lesions between the color values of ME-NBI images and pathological images was at least 0.744. The median AUC, accuracy, sensitivity, specificity, PPV and NPV of test 2 were significantly improved compared with that of test 1 in all endoscopists, junior and experienced groups. Conclusions: The “pink pattern” visualized in ME-NBI images is highly correlated with the nucleus-to-plasma ratio change of gastric epithelial cells, and it can be considered as a useful marker for the diagnosis of the differentiated EGC.